Parents' Weekend. Photo 001 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Parents' Weekend. 'Are You Ready, My Sister?' Presented by Underground Railway Theatre. A dramatic performance depicting the historical adventure of Underground Railroad conductor Harriet Tubman and the Quaker women who helped her bring 300 fugitives to freedom. Production by two actresses/puppeteers features dramatic scenes and live music based on the spirituals of the slave era. Recommended for all ages. In Tisch Library room 304.